PENGARUH BRAND AMBASSADOR, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK EMINA : (STUDI KASUS PADA MAHASISWI DI KOTA MATARAM) - Baiq Sri Atika Dewi; I Made Suardana; Satriawan Satriawan (Kompeten: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of brand ambassadors, brand image, and product quality on purchasing decisions for Emina cosmetic products (a case study on female students in Mataram city). This research variable consists of 3 (three) independent variables, which are brand ambassador (X1), brand image (X2) and product quality (X3) and the dependent variable is purchase decision (Y). The population of this research is public and private university students in Mataram city who use Emina cosmetic products. The sampling technique used in this study is non-probability sampling with the sampling method, namely incidental sampling. The number of samples in this study were 60 respondents. The data analysis technique used is multiple linear regression analysis using the SPSS 28 program. Based on the results of the multiple linear regression test, it can be concluded that the constant value is 3.127, meaning that if there is no change in the brand ambassador variable, brand image and product quality (value X1, X2, and X3 is 0), then the purchase decision on Emina cosmetic products is 3,127 units. The results of this study also show that based on the t test the brand ambassador variable and product quality partially have a significant influence with the results of the t count, namely brand ambassador 2,367 and product quality 5,086 on purchasing decisions, while the brand image variable is seen from the t test that the t table is more greater than t arithmetic means that this indicates that the brand image variable does not have a significant effect on purchasing decisions. Based on the t test, it can be seen that the biggest influence of all variables is the product quality variable, meaning that the product quality variable has the most dominant influence on purchasing decisions with a value of 5.086. According to Beta test, it known that product quality (X3) has the highest value among other independent variables with a value 57.7%. The results of this study also show that based on the F test (simultaneous) the brand ambassador variable, brand image, and product quality have a joint influence on the purchasing decision variable with a value of 23.133.